Identification of Types of Locally Cultivated Food Crops by the Mandar Community in Majene Regency, West Sulawesi Province - Ramlah, Ramlah; Nasir, Yusrianto; Namira, Namira (Jurnal Biologi Tropis, 2025)
This study identifies the types of locally cultivated food crops of the Mandar people in Majene Regency, West Sulawesi. The Mandar people possess local agricultural wisdom passed down through generations, playing a vital role in food security and cultural identity. However, agricultural modernization threatens the sustainability of local plant practices and diversity, making documentation crucial for knowledge preservation and food security. Ethnobotanical methods were used through field surveys, participant observation, and in-depth interviews with farmers and community leaders. Taxonomic identification and confirmation were conducted using https://identify.plantnet.org/id; https://www.plantamor.com/. Data included local names in the Mandar language, cultivation techniques, planting patterns, seasons, and local uses. The results show that the Mandar people maintain various types of food crops, including local rice, local corn, tubers, vegetables, nuts, and local fruits. Each plant has a specific local name reflecting its characteristics. The cultivation system implements polyculture and sustainable crop rotation, with in-depth knowledge of seed selection, organic land management, and natural pest control. The Mandar people still maintain food crop diversity through a sustainable and adaptive cultivation system. This local knowledge is a valuable asset for food security and agrobiodiversity that needs to be documented, revitalized, and integrated with modern agriculture.